The effect of Tocilizumab on the course and outcome of the disease in patients with COVID-19 pneumonia - experience of a secondary-level hospital - Pavic, Sladjana M; Slovic, Radomir; Novkovic, Aleksa; Pavic, Aleksandra (Medical Gazzette, 2026)
Introduction: The significant role in the progression of COVID-19 pneumonia is played by IL-6. Tocilizumab is a monoclonal antibody that blocks its activity.The aim was to assess the effect of tocilizumab on the clinical course, laboratory parameters, radiographic changes in COVID-19 pneumonia, and predictors of mortality.Methods: A retrospective analysis was conducted on data from 340 patients with COVID-19 pneumonia treated with tocilizumab. Data were collected on the day of tocilizumab administration and five days later. Information on sex, age, clinical course, disease outcome, comorbidities, nosocomial infections, oxygenation method, and radiographic changes was gathered. Parameters were compared based on mortality outcomes. Statistical analysis was performed using the SPSS statistical package, v.25.0.Results: The mean age of patients was 66.22 ± 11.37 years, with 66.4% being male. 65.4% had comorbidities, most commonly arterial hypertension (56.2%). Nosocomial infections were present in 8.5%, bacterial pneumonia being the most frequent (34.5%). Oxygen support was non-invasive in 64.1% of cases, and 24% required mechanical ventilation. 23.8% of patients had an R/F index 65 years old. 75.7% of deceased patients had very severe CXR-SS.Conclusion: Tocilizumab led to improvements in respiratory function and regression of biochemical inflammatory parameters. Age >65, comorbidities, and nosocomial infections were associated with higher mortality, with significant radiographic changes and mechanical ventilation being key predictors of mortality.
Keywords: Tocilizumab; COVID-19 pneumonija; clinical course; predictors of fatal outcome